Epidemiology of Leptospira spp. infection in a beef cattle area of Argentina - Mazzanti, Mariana; Scialfa, Exequiel; Rivero, Mariana; Passucci, Juan (Frontiers in Veterinary Science, 2023)
Leptospirosis is an infectious disease caused by pathogenic Leptospira that affects humans and animals. Owing to the complexity and non-eradicable nature of this zoonotic disease, it is necessary to understand this agent's epidemiology in different environments in order to implement prevention and control measures. The main transmission source is indirect, through the contaminated urine of asymptomatic animals that remains in the environment and can be a source of infection for other susceptible animals. In this work, a cross-sectional serological survey was conducted to estimate the seroprevalence of Leptospira infection in beef cattle in Tandil and Ayacucho Departments (Buenos Aires Province) and to identify risk factors and spatial clusters associated with seropositivity. Bivariate and multivariate analyses were performed and 73 out of 375 cows were seropositive, representing a positivity rate of 19.47% (95% CI: 10.51–28.42), with Sejroe and Pomona being the most reactive serogroups: 9.33 % (95% CI: 6.26–12.41) and 8.27 % (95% CI: 5.35–11.19), respectively. The predial seroprevalence in Ayacucho was 80% (95% CI: 59.05–100.95) and in Tandil 60% (95% CI: 28–92.01) although the differences were not statistically significant. (p>0.05). After the Generalized Linear Mixed Model (GLMM) with random effect of farm-level risk, the presence of lagoons (OR: 7.32, 95% CI: 1.68–31.8, p<0.05) and soils with predominantly high and middle slope (OR: 0.24, 95% CI: 0.07–0.74, p<0.05) were associated with bovine leptospirosis. Four spatial clusters with higher rates of seropositivity were detected. A new GLMM was performed with the significant variables detected in the first GLMM and a new variable, "being inside the spatial cluster", being the only one that remained significant (OR: 9.58, 95% CI: 3.39–27.08, p<0.0001). The animals inside the clusters belonged to farms with a greater presence of streams (OR: 9.03, 95% CI: 3.37–24.18, p<0.0001), higher accumulated rainfall (OR: 1.01, 95% CI: 1–1.01, p<0.0001) and soils with fewer high and middle slopes (OR: 0.18, 95% CI: 0.10–0.35, p<0.0001). We conclude that Leptospira is seroprevalent in beef cattle in Tandil and Ayacucho Departments, especially in the latter, where the largest cattle farms are located. In turn, environmental risk factors best explained the detection of seropositive animals.